Pengembangan Media Pansus Raja (Papan Susun Aksara Jawa) unttuk Pembelajaran Aksara Jawa Siswa Kelas III Sekolah Dasar di Kabupaten Semaranng - Setiyani, Angela Wyda; Sukoyo, Joko; Hardyanto, Hardyanto (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Students of Grade III of Elementary school began to be taught Javanese script. The student has some problems when studying Javanese script that is difficult to distinguish and the use of media of learning of Javanese script is limited. Based on these problems found the idea of developing the media of Pansus Raja for the learning of third-grade students of Elementary School in Semarang regency. The problems in this research are: (1) how the needs of teachers and students of the third grade of Elementary school in Semarang regency to Pansus Raja, (2) how to develop the media of Pansus Raja, and (3) how to validate expert lecturers. The method used in this research is Research and Development (RnD) using a data analysis technique that is descriptive qualitative technique. After Pansus Raja was created, then tested to the expert lecturers. The revitalized Pansus Raja tried out to Elementary School. The result of the trial is the media Pansus Raja proved to increase students' understanding of Javanese script.